Photoionization of P+: Experiment and theory. (January 2017) - Nahar, S.N.; Hernández, E.M.; Hernández, L.; Antillón, A.; Morales-Mori, A.; González, O.; Covington, A.M.; Chartkunchand, K.C.; Hanstorp, D.; Juárez, A.M.; Hinojosa, G.
Abstract: An experimental and theoretical study of the single photoionization cross section of the P + cation of phosphorus is presented. Photoionization (PI) cross sections are instrumental for the determination of abundances in the interstellar medium. The experiment was performed by merging an ion beam with a photon beam. The photon beam was nearly monochromatic and had an energy resolution of 24 meV. Calculations were carried out using the Breit–Pauli R -matrix method. The combined study was developed in the photon energy interval from 18 eV (68.9 nm) to 50 eV (24.8 nm). Comparison between the measured and the calculated cross section shows good agreement in general and identifies features of the process and existence of states in the experimental beam. The present results should provide for more accurate modeling of P + . Abstract : Highlights: Detailed features in photoionization of low lying levels of P + . Benchmark the features with state-of-the-art experiment and theory. Found unexpected sharp resonances at threshold due to relativistic effect. Found broad resonant structures in low energy region of the ground state. Results will provide diagnostics of P + in astrophysical plasma.